2017
DOI: 10.1016/j.jcin.2017.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Nonculprit Stenosis Evaluation Using Instantaneous Wave-Free Ratio in Patients With ST-Segment Elevation Myocardial Infarction

Abstract: Acute iFR evaluation appeared valid for ruling out significant nonculprit stenoses in patients with STEMI undergoing primary percutaneous coronary intervention. The time interval from acute to follow-up iFR influenced classification agreement, suggesting that inherent physiological disarrangements during STEMI may contribute to classification disagreement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 25 publications
3
42
0
Order By: Relevance
“…The iSTEMI results and clinical characteristics of the participants have been presented previously . The iSTEMI trial included 120 patients with staged iFR and FFR data available for 146 lesions in 112 patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The iSTEMI results and clinical characteristics of the participants have been presented previously . The iSTEMI trial included 120 patients with staged iFR and FFR data available for 146 lesions in 112 patients.…”
Section: Resultsmentioning
confidence: 99%
“…The iSTEMI study was a prospective international multicenter study including STEMI patients with NCLs. Inclusion and exclusion criteria have been described previously . NCLs were evaluated with iFR in the acute setting and with iFR and FFR at a staged procedure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…artery lesions, which encompassed a total of 10 trials with 2285 patients, the reduction in the risk of cardiovascular events was observed irrespective of the timing of non-infarct-related coronary artery revascularization. 13 Moreover, the iFR in ST-segment Elevation Myocardial Infarction (iSTEMI) trial suggested that physiological disarrangements in STEMI patients affect functional assessment of non-culprit lesions for at least 5 days while reevaluation more than 2 weeks after STEMI may yield a physiological assessment comparable to stable conditions (Thim et al 14 …”
Section: Non-culprit Lesion Treatment In Stsegment Elevation Myocardimentioning
confidence: 99%